The Significance of Competence, Human Resource Development, and Organizational Culture on Employee Performance at BPJS Ketenagakerjaan in Makassar City - Sulfathurrahmah Syarif; Agussalim Harrang; Muhammad Ikram Idrus; Ahmad AC Ahmad AC; Maklassa Maklassa (Eduvest - Journal of Universal Studies, 2024)
In the era of globalization and rapid technological development, organizational performance is highly dependent on the quality of human resources. In order to achieve its strategic goals, organizations such as BPJS Employment require employees who have high competence, skills and competitiveness to improve their performance. This study aims to determine and analyze the effect of competence, human resource development and organizational culture on the performance of employees of BPJS Ketenagakerjaan Makassar City. This study used a quantitative method involving 77 respondents, whose data were collected through questionnaires. Data analysis was carried out using multiple linear regression with the help of SPSS V.24 software. The results showed that employee competence has a positive but insignificant effect on performance, while human resource development and organizational culture each showed a positive and significant effect on employee performance, with a confidence level of 95%.